Perlindungan Hukum terhadap Harta Influencer di Bawah Umur - Azzahra, Sheika; Sembiring, Rosnidar; Azwar, Tengku Keizerina Devi; Yefrizawati, Yefrizawati (ARBITER: Jurnal Ilmiah Magister Hukum, 2024)
This research aims to determine and analyze the legal protection of the personal property of underage influencers The type of research used is normative legal research, specifically by examining or dissecting optional information as legal material, especially important legal material, and additional legal material, by understanding regulation as a set of guidelines or positive standards in a common set of laws. The exploratory idea used in this exam is analytical descriptive research on the legal relationship of underage influencers with their service providers. Underage influencers have a different legal status compared to adult influencers. Legal protection of the personal property of underage influencers. The law provides special protections for minors, including protection of their personal property as influencers. This protection includes a guardian to protect property.